SCUAF Version 4: a model to estimate soil changes under agriculture, agroforestry and forestry - Young, A.; Menz, K.; Muraya, P.; Smith, C. (Australian Centre for International Agricultural Research, 1998)
Soil Changes Under AgroForestry (SCUAF) is an easy-to-use computer model which predicts the effects of specific land use systems under given environmental conditions. It includes the distinctive features of agroforestry, namely land use systems which include both trees and crops. However, it can also be used to compare agroforestry systems with land use under agriculture or forestry, treating these as limiting cases of agroforestry. Hence, SCUAF can alternatively be construed to mean Soil Changes Under Agriculture, agroforestry and Forestry. SCUAF is a process-response model in which the user specifies the physical environment, land use system, initial soil conditions, initial rates of growth and rates of operation soil - plant processes. The model provides an annual simulation of changes in soil conditions and the effects of soil changes upon plant growth and harvest. It is primarily intended for simulation over periods of 10-20 years but can be applied to long-term simulation. This document describes the fourth version of the SCUAF model.